The microprocessor-controlled duplex lift system - Özcan, Abdulkadir. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The application areas qf microprocessors have been growing recently. In addition to various areas, efficient and reliable results can be obteined in duplex elevator control systems. The object of this thesis is to apply microprocessor control on a duplex lift system. Lifts, as known, transport passengens between floors upwards or downwards; consequently these systems dissipate much power. Most of the power is spent by lti.ft motors and partially by control units. The aim of the thesis is to construct a more powerful control system reducing the pqy,er consumption and increasing the reliability. Since all logic combinations are considered the performance of the duplex lift system is maximized, the waiting time of passengers is minimized, thus up-down traffic speed is increased.
Keywords: Microprocessors.; Elevators.